Multiple versus singular presentation of television commercials (1999)
This study experimentally assessed combined and singular measures of Television (TV) commercial efficacy. Eighty (80) senior secondary (SS) 2 students, randomly selected from two priavte secondary schools in Lagos metropolis, served as subjects. They watched experiment – specific commercials which had presentation, type of stimulus and source credibility as independent variables. Multiple measure consisted of a subject’s aggregate score on recall of advertised product information, attitude towards and intention to try advertised product. Singular measures were the individual scores on recall of advertised product information, attitude towards and intention to try advertised product. A ten item standardized questionnaire measured advertised product information while Belch’ s (1981) standardized differential scales measured attitude towards anti intention to try advertised product. Using Analysis of Variance (ANOVA) as tool for analysis, it was found that although there were some significant effects of the independent variables on the singlular measures of efficacy, their effects on the combined measures (efficacy) were strongest and more encompassing. The implication was that advertisers stand better chances of getting true advertising results when combined measures of efficacy are used than when singular measures are used